A penny's worth of character - Stuart, Jesse 1907-; Henneberger, Robert (New York Whittlesey, 1954)
Shan is dishonest with the storekeeper in his rural Kentucky community, but he feels better about himself after his mother forces him to put things right.
Keywords: Honesty -- Fiction; Kentucky -- Fiction